2021
DOI: 10.13005/bpj/2161
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Antioxidant Enzymes Activities and Lipid Peroxidase Level in Tissues of Stress-induced Rats

Abstract: Background: Estimating the changes in the levels of oxidative stress biomarkers are vital in identifying stress related disease in living organism. This study examined changes in the activity of antioxidant enzymes and lipid peroxidase level in female Wistar rats exposed to stressors of different nature were examined. Methods: 88 apparently healthy rats within the ages of 8-12weeks and weighing between 120-180g were utilized for the study. Rats were acclimatized for 2weeks and fed with rat chaw and water ad li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…This study also reported that significant reduction in litter size after 6 hrs of exposure to stress before mating when, however, treatment of stressed rats with CC was able to increase litter size towards normal, but not up to the litter size of the CC treated unstressed rats. This finding was consistent with the findings of Chukwuebuka et al 43 , who reported a reduction in litter size of pregnant stressed rats exposed to restraint, mirror and intruder stress model at 3 hrs/day for 3 weeks when compared with the litters of stressed rats that were improved when treated with CC. This study was also consistent with the report by Euker and Riegle 39 that exposure to restraint stress for 2 hrs for the first 5 days of pregnancy can decrease the average litter size in rats.…”
Section: Discussionsupporting
confidence: 93%
“…This study also reported that significant reduction in litter size after 6 hrs of exposure to stress before mating when, however, treatment of stressed rats with CC was able to increase litter size towards normal, but not up to the litter size of the CC treated unstressed rats. This finding was consistent with the findings of Chukwuebuka et al 43 , who reported a reduction in litter size of pregnant stressed rats exposed to restraint, mirror and intruder stress model at 3 hrs/day for 3 weeks when compared with the litters of stressed rats that were improved when treated with CC. This study was also consistent with the report by Euker and Riegle 39 that exposure to restraint stress for 2 hrs for the first 5 days of pregnancy can decrease the average litter size in rats.…”
Section: Discussionsupporting
confidence: 93%
“…The above-mentioned antioxidant enzymes like SOD, Px and CAT were considered biologically important in diminution of free radical like hydrogen peroxide (Lin, et al, 2018). In diabetic rats antioxidant enzyme activities of SOD, Px and CAT were decreased in our present findings like our previous publication (Maiti et al, 2015) along with observation of other (Chukwuebuka et al, 2021). On the other hand said antioxidant enzyme activities were resettled towards control levels after administration of seed of T. indica and glibenclamide.…”
Section: Discussionsupporting
confidence: 85%
“…However, in the present study, the administration of MC along with MTX exhibited no significant difference in the serum levels of MDA, CAT, and SOD in contrast to other studied groups. The variations in the levels of oxidative stress biomarkers may be linked to the kind and severity of stressors that seem to be the principal factor in determining oxidative stress measurement in rats as recorded in a previous study [28].…”
Section: Discussionmentioning
confidence: 87%